Strategy To Increase Micro, Small And Medium Enterprises (Msmes) Through The Role Of Sharia Financial Institutions In KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang Branch - Aji, Muhammad Galih; Sukardi, Didi; Bushtomi, Achmad Otong (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
The purpose of this study is to find out how KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang Branch implements strategies to improve Micro, Small and Medium Enterprises (MSMEs) and to find out the obstacles and efforts in implementing strategies to improve the Micro, Small and Medium Enterprises. The results of this study are that KSPPS Al-Ishlah plays a role in terms of improving the business of MSME actors for members and the community around KSPPS, the income of cooperative members increases, especially MSME actors, reviving businesses that are almost dead or declining and reducing unemployment rates, and there are several obstacles faced by KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang branch towards improving MSMEs, namely the increasing number of members, installments that are stuck from members which cause capital turnover to be hampered and the limited capital owned by MSME cooperatives.